Effects of movement sequence on the performance of javelin throwing - Liu, H.; Leigh, S.; Yu, B. (ISBS - Conference Proceedings Archive (Konstanz), 2010)
The sequence of joint and segment movements during delivery phase is believed to significantly affect on the performance of javelin throwing. Literature reported that elite javelin throwers showed a proximal to distal sequence of joint center maximum linear velocities (Whiting et al., 1991; Best et al., 1993; Mero et al., 1994; Bartlett et al., 1996). The sequence of maximum joint center linear velocities, however, does not necessarily represent the sequence of joint or segment movements. The purpose of this study is to determine the effects of the sequence of upper extremity joint and segment angular movements on the performance of javelin throwing.